East Java Government Instagram Content Analysis: Unpacking the Relationship Between Content Types and Public Engagement in 2023 - Sukma, Alifian; Aji, Gagas Gayuh (Sharia Business Management UIN Raden Intan Lampung, 2024)
This study analyzes the online interactions of government Instagram accounts in East Java, Indonesia, focusing on the effectiveness of different content types on this social media platform. Digital platforms, particularly social media, have become crucial for government performance measurement and public interaction. Governments in Indonesia use social media, specifically Instagram, to disseminate information, socialize organizational performance, and channel public aspirations.The research involved collecting data from 37 government Instagram accounts in East Java for the year 2023 using the Virol application. The study reviews the literature on digital platforms and social media in governance, highlighting the preference for visual content among followers and the importance of information quality in building citizen trust. The study also notes the positive impact of social media utilization on public satisfaction with government institutions.Data reveal that album posts are the most frequent (average of 1613.78 posts), followed by images (1121.57), videos (241.03), and IGTV (147.68). In terms of engagement, album posts received the highest average likes (219.6), while IGTV received the most comments (4.6 on average).The findings suggest that followers prefer album posts and that IGTV content generates more in-depth discussions. The study recommends that government social media strategies prioritize album posts for broader engagement and use IGTV for more detailed content that encourages public discussion.This research contributes to understanding the dynamics of government-public interaction through Instagram and provides actionable insights for enhancing digital communication strategies.